Does soil type influence the occurrence of fire outbreaks in Cerrado, Brazil? - Gilsonley Lopes dos Santos; Iris Cristiane Magistrali; Renato Sinquini de Souza; Rafael Coll Delgado; Marcos Gervasio Pereira (Soil Advances)
Forest fires associated with anthropic activities in Cerrado, Brazil, have been the main cause of the degradation of the biome. Thus, this study aims to understand the dynamics of fire foci and Gross Primary Production as a function of soil classes in an Environmental Preservation Area. This study combined soil types with meteorological variables of rainfall, soil moisture and air temperature to relate to fire occurrences and Gross Primary Production (GPP) for the years 2001–2020. For the evaluated period, there was an increase in temperature (±0.5 ºC) and a reduction in rainfall (±50 % in the driest years). The highest numbers of fire outbreaks were recorded in the areas corresponding to the Neossolos (Arenosols), followed by Latossolos (Ferralsols) between August and October. The future projection of the occurrence of foci for the next 10 years indicated that there would be an increase in the number of fire foci in all soil classes (700 %), especially for Neossolos. The future projection of GPP for the next 10 years indicates that there would be a reduction in coverage, especially for Gleissolo (Gleysol, 40–80 %). As a prevention strategy, attention should be doubled between August and October, as these months are the most conducive to fire outbreaks in the Cerrado.